Optimizing the dose-averaged linear energy transfer for the dominant intraprostatic lesions in high-risk localized prostate cancer patients - Bo Zhao; Nobuyuki Kanematsu; Shuri Aoki; Shinichiro Mori; Hideyuki Mizuno; Takamitsu Masuda; Hideyuki Takei; Hitoshi Ishikawa (Physics and Imaging in Radiation Oncology)
Background and purpose: Radiotherapy for localized prostate cancer often targets the entire prostate with a uniform dose despite the presence of high-risk dominant intraprostatic lesions (DILs). This study investigated the feasibility of focal dose-averaged linear energy transfer (LETd) boost for prostate carbon-ion radiotherapy to deposit higher LETd to DILs while ensuring desired relative biological effectiveness weighted dose coverage to targets and sparing organs at risk (OARs). Materials and methods: A retrospective planning study was conducted on 15 localized prostate cancer cases. The DILs were identified on multiparametric MRI and used to define the boost target (PTVboost). Two treatment plans were designed for each patient: 1) conventional plan optimized by the single-field uniform dose technique, and 2) boost plan optimized by the multifield optimization and LET painting technique, to achieve LETd boost within the PTVboost. Dose and LETd metrics of the targets and OARs were compared between the two plans. Results: Compared to the conventional plans, the boost plans delivered clinically acceptable dose coverage (D90% and D50%) to the target (PTV2) within 1% differences while significantly increasing the minimum LETd by 16 ∼ 24 keV/μm for the PTVboost (63.9 ± 2.8 vs. 44.0 ± 1.3 keV/μm, p < 0.001). Furthermore, these improvements were consistent across all cases, irrespective of their anatomical features, including the boost volume’s size, location, and shape. Conclusion: Focal LETd boost was a feasible strategy for prostate carbon-ion radiotherapy. This investigation demonstrated its superiority in delivering LETd boost without depending on tumor location and volume across different cases.